(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The integration of a country into the global economy necessitates the production of products that conform to international standards. Achieving this requires the modernization of production processes, the introduction of new technologies, and the re-equipment of facilities. The data presented reveals that during the period of 2019-2023, JSC “Galla-Alteg” incurred significant expenses due to the write-off of fixed assets that were rendered unusable, which amounted to 25% of the total fixed assets. The joint-stock company also accumulated unused capital assets, which exceeded 1% of the total fixed assets. To address this issue, the company invested 74% of its main equipment budget to purchase and lease new equipment, replacing outdated machinery. Notably, in 2022, the company acquired a new grain processing technology, worth 9,770,353 thousand sums, resulting in increased production of high-quality, cost-effective products. This modernization has proven to be a wise investment, leading to a reduction of production costs by 15%.